(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Rural market in India has been grown faster than ever in previous decade. In different parts of country, the villages have seen transformation. The government of all the parties in different states had it clear in their minds that if villages will not grow the growth of state in not possible. Some credit can be given to consumerism too. The urban market is becoming saturated, whereas villagers have plenty of disposable income thanks to bumper harvests in recent years. Rural markets are estimated to have three times the potential of the European market. This clearly defines the amount of business that can be generated in rural Indian markets. For quite some time, the allure of rural India has been the subject of intense debate among corporate executives. With increased rural literacy and media exposure, people in rural areas are becoming more conscious of their purchasing decisions, just like their urban counterparts. This makes it even more difficult for businesses to comprehend the rural consumer’s purchasing habits, consumption patterns, and needs and desires. This thesis follows the path of rural marketing. It goes on to discuss the challenges that companies face when marketing their products, as well as the strategies that companies can use to overcome these challenges.